Gender dynamics, women’s empowerment, and diets: Qualitative findings from an impact evaluation of a nutrition-sensitive poultry value chain intervention in Burkina Faso - Eissler, Sarah; Sanou, Armande; Heckert, Jessica; Myers, Emily; Nignan, Safiatou; Thio, Elisabeth; Pitropia, Lucienne Amélie; Ganaba, Rasmané; Pedehombga, Abdoulaye; Gelli, Aulo (International Food Policy Research Institute, 2020)
The SELEVER study is a five-year impact evaluation designed to address key knowledge gaps on the impact of a poultry value chain intervention on the diets, health, and nutritional status of women and children in Burkina Faso. This report qualitatively examines the SELEVER program’s impact on women’s empowerment and intra-household gender dynamics in relation to food production and allocation, as well as control and use over poultry resources in the study areas. Six villages across five provinces were purposively selected for this study. Data were collected using multiple qualitative methods. In each village, we conducted four sex-disaggregated focus group discussions, and semi-structured individual interviews were held with a man and a woman from two different households. Sex-disaggregated seasonal calendars were created for half of the villages. Interviews were also conducted with project service providers in each community, including group leaders (n=13), voluntary vaccinators (n=10), and poultry traders (n=6). A mix of inductive and deductive thematic coding guided the analysis of the data. Men and women participants described an empowered woman in terms of her confidence, how she spent her time, financial capacity, and freedom of movement. SELEVER beneficiaries illuminated how gender norms were shifting related to household activities and women’s empowerment, such that young boys are now washing dishes and women earn additional incomes from raising her own poultry. Yet results suggest that women’s empowerment may threaten men and their masculinity, an important tension of which SELEVER and other projects should be cognizant. Participants perceived that while SELEVER has increased women’s access to the necessary resources and capacity to raise quality poultry, and their incomes, women still lack full latitude to make decisions around when to sell or kill their bird. Instead they must rely on their husbands’ permission. Beneficiaries are more aware of the benefits of consuming poultry products, yet barriers persist for actual consumption. This report further details the intersectional nature of these findings, which will be important to consider. The differences in women’s role in monogamous versus polygynous households is especially important to consider in interpreting the program impacts and further strengthening the program delivery activities. The SELEVER program has improved outcomes for women across the village sites in terms of empowerment, awareness raising, and behavior change. Yet barriers and challenges, often rooted in social norms, persist for women’s involvement in poultry production, their empowerment, and the potential for the SELEVER program to improve diets of household members.